ChemInform Abstract: Synthesis of Bis‐ and Tris(3‐H‐1, 3‐azaphospholo)benzenes. Issue 28 (15th July 2014) - Marchenko, Anatoliy; Koidan, Heorgiy; Huryeva, Anastasiya; Smaliy, Radomyr; Vlasenko, Yurii; Gutov, Oleksii; Kostyuk, Aleksandr
Abstract Surprisingly, the double and the triple intramolecular cyclocondensation proceeds more efficiently than previously reported reaction involving monoaminobenzene derivatives.